2002
DOI: 10.1142/s0217732302008460
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Constant and Torsion

Abstract: Riemann–Cartan space–time U4 is considered here. It has been shown that when we link topological Nieh–Yan density with the gravitational constant, we then obtain Einstein–Hilbert Lagrangian as a consequence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 16 publications
(8 reference statements)
0
23
0
Order By: Relevance
“…The space time manifold now corresponds to the de Sitter space M 4,1 . In this framework SO(4, 1) Pontryagin density can be written as [23,29] …”
Section: Topological Densities and Gravity Lagrangianmentioning
confidence: 99%
See 2 more Smart Citations
“…The space time manifold now corresponds to the de Sitter space M 4,1 . In this framework SO(4, 1) Pontryagin density can be written as [23,29] …”
Section: Topological Densities and Gravity Lagrangianmentioning
confidence: 99%
“…Recently, it has been shown that [23], in U 4 space one can locally consider a particular term from this SO(4, 1) Pontryagin density as the gravitational Lagrangian [30], given by…”
Section: Topological Densities and Gravity Lagrangianmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus de Sitter gauge theory comes up as the corrected Poincare gauge theory [5]. Recently a gravitational Lagrangian has been proposed [6], where a Lorentz invariant part of the de Sitter Pontryagin density has been treated as the Einstein-Hilbert Lagrangian. In this formalism the role of torsion in the underlying manifold is multiplicative rather than additive and the Lagrangian looks like torsion⊗curvature.…”
Section: Introductionmentioning
confidence: 99%
“…† † The same connection with different gravitational dynamics has also been studied (See, e.g., Refs. [39][40][41][42][43][44][45][46][47][48][49][50] which are defined as:…”
mentioning
confidence: 99%